First Mover Advantage in Ecommerce - Sharif, Abdulaziz (2009)
In order for any innovative firm to reap the rewards of their labour, they must employ a strategy that utilises the opportunity that their innovation generates. Often, highly innovative firms become first movers, having to not only to develop the innovation but also the market for that innovation.